(untitled) (Acta Horti Botanici Bucurestiensis, 2024)
The concept of urban flora refers to the plant life that exists within city environments, encompassing the types of plants found in urban areas and how they interact with the unique challenges and conditions here (e.g. anthropic habitats with limited and controlled space, pollution, heat, drought), which can favour some species and restrict others. The first references to the Bucharest’s flora date from 1876, and since then the dynamics of the number of species registers a continuum. As a result of the implementation of “UrbFloraBuc” project during 2023-2024, we report 12 new species of which five are native and seven are allochthonous, and data on their distribution and habitats within the city. This study makes valuable contributions to the knowledge of Bucharest flora, emphasizing, on the one hand, the importance of the urban environment as a conservation space for rare (native) species, and on the other hand, raising an alarm signal on the need for an early detection of the allochthonous species, to the extent that the latter could become problematic in the urban environment.